An Evaluation of Car-Ownership and Car-Usage Policies in Singapore - PHANG, Sock-Yong (Institutional Knowledge at Singapore Management University, 1990)
Report presented to Parliament 2 January 1990 as part of Select Committee on Land Transportation Policy. Covers the transportation policies of Singapore from 1960s to 1980s. Analysis of car ownership policies, including PARF. Analysis of car usage policies.